Financial Feasibility Analysis of Cashew Agroindustry in Kendari City, Southeast Sulawesi Province - Asriani, Asriani (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
This study aims to analyze the financial feasibility of cashew agro-industry in Kendari City, Southeast Sulawesi Province. To select key informants carried out deliberately (purposive), namely the criteria of people or other parties who know about the cashew industry, experienced, know in detail about this business, and know the surrounding conditions. The informants chosen in this study are the owners of the cashew industry and related government agencies. Data analysis techniques used are (1) Benefit-Cost Ratio (BCR) analysis; (2) Net Present Value (NPV) analysis; and (3) Internal Rate of Return (IRR) analysis. The results obtained by the BCR value of 1.315, the NPV value obtained by 373.253.360, and the IRR value of 30%. Based on the value of the three criteria used, it shows that cashew agroindustry in Kendari City is financially feasible to be developed